2016
DOI: 10.1021/jacs.5b10307
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Protein Folding and Topology from a Computational Transfer Free Energy Scale

Abstract: Knowledge of the transfer free energy of amino acids from aqueous solution to a lipid bilayer is essential for understanding membrane protein folding and for predicting membrane protein structure. Here we report a computational approach that can calculate the folding free energy of the transmembrane region of outer membrane β-barrel proteins (OMPs) by combining an empirical energy function with a reduced discrete state space model. We quantitatively analyzed the transfer free energies of 20 amino acid residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 71 publications
(213 reference statements)
4
36
1
Order By: Relevance
“…Although it was previously shown that LFRs of the hydrophobic core is the main driving force for TMBs to be inserted into membrane [20], interestingly, we observed that the TFEs of hydrophobic core never reach their minimum when TMBs are fully inserted in all 52 cases, while TFEs of the whole TMBs reach their minimum at the fully inserted position (step 0). The "W" shape free energy curves of the two head group regions indicates that LFRs there act like "energetic latches" to lock TMBs in their fully…”
Section: Cc-by-nc-contrasting
confidence: 54%
See 4 more Smart Citations
“…Although it was previously shown that LFRs of the hydrophobic core is the main driving force for TMBs to be inserted into membrane [20], interestingly, we observed that the TFEs of hydrophobic core never reach their minimum when TMBs are fully inserted in all 52 cases, while TFEs of the whole TMBs reach their minimum at the fully inserted position (step 0). The "W" shape free energy curves of the two head group regions indicates that LFRs there act like "energetic latches" to lock TMBs in their fully…”
Section: Cc-by-nc-contrasting
confidence: 54%
“…Particularly, GeTFEP-mid has a r = 0.87 correlation with MFscale, which was measured using a TMB, OmpLa, as the host system. GeTFEP-mid correlates with the computational OmpLa scale [20,21] as well with r = 0.90 (Fig. S3).…”
Section: Comparison With Previous Hydrophobicity Scalesmentioning
confidence: 73%
See 3 more Smart Citations